POLLUTION AND HUMAN HEALTH - Nargesh, P.S. (International Journal of Research -GRANTHAALAYAH, 2015)
There are Literally Thousands of sources of these gases. Scientific evidence indicates that ground level – ozone not only affects people with impaired respiratory systems, but healty adults and children as well. Nature and sources of the pollutant effects on human health and the environment. Increased combustion of fossil fuels in the last century is responsible for the progressive change in the atmospheric composition. Air pollutants, such as carbon monoxide (CO), sulfur dioxide (SO2), nitrogen oxides (NOx), volatile organic compounds (VOCs), ozone (O3), heavy metals, and respirable particulate matter (PM2.5 and PM10), differ in their chemical composition, reaction properties, emission, time of disintegration and ability to diffuse in long or short distances. Air pollution has both acute and chronic effects on human health, affecting a number of different systems and organs. It ranges from minor upper respiratory irritation to chronic respiratory and heart disease, lung cancer, acute respiratory infections in children and chronic bronchitis in adults, aggravating pre-existing heart and lung disease, or asthmatic attacks. These effects of air pollutants on human health and their mechanism of action are briefly discussed.